Design thinking pedagogy facilitating innovation and impact in tertiary education - Wrigley, Cara; Mosely, Genevieve (Routledge, an imprint of the Taylor & Francis Group, 2023)
The problems facing society today are complex, multifaceted, and require crossing multiple disciplinary boundaries. As such, these problems call for interdisciplinary collaboration, including new and different combinations of skills and knowledge. Currently, tertiary education providers are not well-positioned to develop these interdisciplinary capabilities at a rate commensurate with the speed of contemporary change. This book places design thinking as the catalyst to create change in the tertiary education sector and to build interdisciplinary skill sets that are required for the graduate of the future. By presenting a series of case studies and drawing on global experts in the field, this book investigates pedagogical approaches, disciplinary facilitation practice, curriculum integration, and a framework for understanding design thinking pedagogy within tertiary education. Focusing on how educational institutions can produce innovative graduates with the ability to traverse disciplinary constraints, this book will be essential reading for research students, academics, and industry practitioners.